Analisis Pengalaman Pengguna dalam Resolusi Sengketa pada Platrom Fintech - Siti Jolehah; Fatikah Fatikah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The rapid development of the financial technology (fintech) industry has brought various innovations in financial services, but also poses challenges related to conflict resolution between users and service providers. This study aims to analyze the user experience in resolving disputes through fintech platforms, with a focus on the effectiveness of existing dispute resolution mechanisms. The method used in this study is a qualitative approach with in-depth interviews with active users of fintech platforms who have been involved in disputes. The results of the study show that although fintech platforms provide various channels for settlement, such as mediation or arbitration, many users complain about transparency, complexity of procedures, and unclear information regarding their rights and obligations in the process. In addition, the trust factor in third parties involved in the settlement is also a major issue. These findings provide insight into the need to improve the resolution system by improving communication between fintech service providers and users, as well as clarifying settlement procedures to create a better user experience. This study is expected to contribute to the development of policies and regulations related to dispute resolution in the fintech sector. The abstract above includes the background of the problem, research objectives, methods used, research results, and contributions from the research. You can adjust the content or focus of the research based on the specific focus you want to emphasize in your analysis.